Superodontella gladiator, a new species of the family Odontellidae (Collembola: Poduromorpha) from Nepal with extremely elongated mouthparts - Agolin, Mikaël; Houssin, Céline; Deharveng, Louis (Zootaxa, 2009)
Superodontella gladiator, a new Odontellidae species from Nepal, is described with emphasis on its extremely elongated mouthparts, which are unique in the family.